A Novel Missense Mutation in USP26 Gene Is Associated With Nonobstructive Azoospermia. (October 2016) - Ma, Qian; Li, Yuchi; Guo, Huan; Li, Cailing; Chen, Jianbo; Luo, Manling; Jiang, Zhimao; Li, Honggang; Gui, Yaoting
Objective: The aim of this study was to evaluate whether ubiquitin-specific peptidase 26 ( USP26 ) gene variations were associated with nonobstructive azoospermia (NOA). Methods: Seven hundred and seventy-six patients diagnosed with NOA and 709 proven fertile men were included in this study. Genetic variations of infertility-related genes, including USP26, were identified by selected exonic sequencing. The effects of USP26 mutations on androgen receptor (AR) binding, ubiquitination, and transcriptional activity were detected by immunoprecipitation and luciferase assay in Hela and TM4 cells. Results: Six novel missense mutations and 1 novel synonymous mutation of USP26 unique to the patients with NOA were identified. Of these missense mutations, USP26 R344W remarkably reduced the binding affinity and deubiquitinating activity of USP26 to AR, thus eliminated the inhibitory effect of USP26 on transcriptional activity of AR in Hela and TM4 cells. Conclusion: A novel USP26 variant p.R344W is associated with NOA probably through affecting AR function.